Hormone replacement therapy in cancer survivors: Utopia?. (April 2018) - Angioli, Roberto; Luvero, Daniela; Armento, Grazia; Capriglione, Stella; Plotti, Francesco; Scaletta, Giuseppe; Lopez, Salvatore; Montera, Roberto; Gatti, Alessandra; Serra, Giovan Battista; Benedetti Panici, Pierluigi; Terranova, Corrado
Highlights: With the increase of postmenopausal population, the incidence of all cancers is expected to increase. HRT has proven to be highly effective in alleviating menopausal symptoms. According to preclinical data, estrogen and progesterone seems to be involved in the breast and endometrial cancers. Many clinicians don't prescribe HRT due to the fear of relapse and the risk to develop CHD or breast cancer. Before the decision to use HRT an accurate counselling should be mandatory. Abstract: As growing of old women population, menopausal women will also increase: an accurate estimation of postmenopausal population is an essential information for health care providers considering that with aging, the incidence of all cancers is expected to increase. Hormone replacement therapy (HRT) has proven to be highly effective in alleviating menopausal symptoms such as hot flashes, night sweats, dyspareunia, sexual disorders, and insomnia and in preventing osteoporosis. According to preclinical data, estrogen and progesterone are supposed to be involved in the induction and progression of breast and endometrial cancers. Similarly, in epithelial ovarian cancer (EOC), the pathogenesis seems to be at least partly hormonally influenced. Is HRT in gynecological cancer survivors possible? The literature data are controversial. Many clinicians remain reluctant to prescribe HRT for these patients due to the fear of relapse and the risk to develop coronary heart disease or breast cancer. Before the decision to use HRT an accurate counselling should be mandatory in order to individualizing on the basis of potential risks and benefits, including a close follow-up. Nevertheless, we do believe that with strong informed consent doctors may individually consider to prescribe some course of HRT in order to minimize menopausal symptoms and disease related to hormonal reduction.